Effect of twin crystallographic orientation on deformation and growth in Mg alloy AZ31. (December 2020) - Paramatmuni, Chaitanya; Dunne, Fionn P.E.
Abstract: In this study we present an integrated experimental and computational study of the effect of twin crystallographic orientation on local deformation characteristics that govern its subsequent growth. Experimentally measured intra-twin geometrically necessary dislocations (GND) density and twin-resolved shear stress (TRSS) differences within twins are found to vary with twin crystallographic orientation, which is characterised in terms of inclination angle (that between the loading direction and twin c-axis). Shear transformation modelling of four particular twins with increasing inclination angle shows that the latter dominates both slip and TRSS within the twin. Model predictions and experimental measurements show that intra-twin average GND density increases with inclination angle, and that a reversal in the sign of intra-twin TRSS occurs as the inclination angle increases. This implies that the TRSS (backstress) within a twin is not always negative, which further suggests that the rate of twin growth is influenced by its own crystallographic orientation instead of global Schmid factor (which is based on parent grain orientation). Highlights: A reference called twin inclination angle is defined, which is that between twin c-axis and loading direction. The intra-twin GND density and twin-resolved shear stress (TRSS) increase with the inclination angle. A reversal in the sign of TRSS within twin with increase in the inclination angle is observed. This implies that the TRSS (backstress) within twin is not always negative. This indicates that the rate of twin growth depends on twin crystallographic orientation instead of global Schmid factors.